1999
DOI: 10.1103/physrevb.60.1349
|View full text |Cite
|
Sign up to set email alerts
|

Microwave spectroscopy of thermally excited quasiparticles inYBa2Cu3O<

Abstract: We present here the microwave surface impedance of a high purity crystal of Y Ba2Cu3O6.99 measured at 5 frequencies between 1 and 75 GHz. This data set reveals the main features of the conductivity spectrum of the thermally excited quasiparticles in the superconducting state. Below 20 K there is a regime of extremely long quasiparticle lifetimes, due to both the collapse of inelastic scattering below Tc and the very weak impurity scattering in the high purity BaZrO3-grown crystal used in this study. Above 20 K… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
252
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(273 citation statements)
references
References 56 publications
19
252
1
1
Order By: Relevance
“…This is of particular interest in CeCoIn 5 because normal-state transport measurements reveal strong inelastic scattering and non-Fermi-liquid behaviour 25,26 . In the cuprates, where similarly strong scattering is observed in the normal state 27 , electrodynamic measurements show a rapid collapse in quasiparticle scattering on cooling through T c [28][29][30] , indicating that the charge carriers couple to a spectrum of fluctuations of electronic origin, in contrast to the phonons of a conventional metal. Early measurements on CeCoIn 5 are suggestive of similar behaviour 2,17 .…”
mentioning
confidence: 81%
“…This is of particular interest in CeCoIn 5 because normal-state transport measurements reveal strong inelastic scattering and non-Fermi-liquid behaviour 25,26 . In the cuprates, where similarly strong scattering is observed in the normal state 27 , electrodynamic measurements show a rapid collapse in quasiparticle scattering on cooling through T c [28][29][30] , indicating that the charge carriers couple to a spectrum of fluctuations of electronic origin, in contrast to the phonons of a conventional metal. Early measurements on CeCoIn 5 are suggestive of similar behaviour 2,17 .…”
mentioning
confidence: 81%
“…It is instructive to compare the magnitude of τ e in Bi2212 and Y123. In the latter system, τ e of high-quality crystals is of the order of 7 ps [15] and is reported to approach 20 ps [26] in BaZrO 3 -grown crystals. For Bi2212, recent study on the complex conductivity by Corson et al showed the qp lifetime to approach ∼1 ps [27] at low temperatures, similar to the value calculated independently from our measurements.…”
mentioning
confidence: 94%
“…For Bi2212, recent study on the complex conductivity by Corson et al showed the qp lifetime to approach ∼1 ps [27] at low temperatures, similar to the value calculated independently from our measurements. Further, assuming the scattering rate to remain constant [26], one can estimate the size of κ e upward in temperature. The deduced value at 5K (∼4.8 mW/Kcm) can be compared via the Wiedemann-Franz law to the available data on charge conductivity which is limited to T >5K [13].…”
mentioning
confidence: 99%
“…25 In the present case of a 1D semiconducting nanowire proximity coupled to bulk s-wave superconductors, such absorption experiments can be difficult, and another quantity is needed which nevertheless is still given by the real part of the ac conductivity suitably defined. Below we show that the ac Josephson impedance serves this purpose, and it can be easily measured across a 1D semiconducting nanowire contacted by s-wave superconducting leads which also produce the proximity effect (Fig.…”
Section: Bulk Measurement (Ac Response)mentioning
confidence: 99%